Anthocyanin-Containing Purple Sweet Potato (Ipomoea batatas L.) Synbiotic Yogurt Inhibited 3T3-L1 Adipogenesis by Suppressing White Adipocyte-Specific Genes - Ariyanto EF; Shalannandia WA; Lantika UA; Fakih TM; Ramadhan DSF; Gumilar AN; Permana FK; Rahmah AN; Atik N; Khairani AF (Dove Medical Press, 2023)
Eko Fuji Ariyanto,1 Widad Aghnia Shalannandia,2 Uci Ary Lantika,3 Taufik Muhammad Fakih,4 Dwi Syah Fitra Ramadhan,5 Arini Nurisydayanti Gumilar,6 Farhan Khalil Permana,6 Anisa Nadia Rahmah,6 Nur Atik,2 Astrid Feinisa Khairani2 1Division of Biochemistry and Molecular Biology, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jatinangor, West Java, Indonesia; 2Division of Cell Biology, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jatinangor, West Java, Indonesia; 3Department of Biomedical Sciences, Faculty of Medicine, Universitas Islam Bandung, Bandung, West Java, Indonesia; 4Department of Pharmacy, Faculty of Mathematics and Natural Sciences, Universitas Islam Bandung, Bandung, West Java, Indonesia; 5Politeknik Kesehatan Kementerian Kesehatan Makassar, Makassar, Indonesia; 6Undergraduate Program Medical Doctor, Faculty of Medicine, Universitas Padjadjaran, Jatinangor, West Java, IndonesiaCorrespondence: Astrid Feinisa Khairani, Division of Cell Biology, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jalan Raya Bandung - Sumedang Km 21, Jatinangor, West Java, 45363, Indonesia, Tel +62-22-7795594, Email astrid.khairani@unpad.ac.idPurpose: We unravel the effect of anthocyanin-containing purple sweet potato synbiotic yogurt (PSPY) on 3T3-L1 adipocyte differentiation and its fundamental molecular mechanisms.Methods: Molecular docking simulation was performed to observe and identify the affinity and interaction between bioactive compounds and targeted proteins. MDI (isobutylmethylxanthine, dexamethasone, and insulin)-containing medium, a cocktail that stimulates adipogenesis, was used in this study. The toxic effect possibility of the yogurt product was evaluated using 3-[4, 5-dimethylthiazol-2-yl]-2.5 diphenyl tetrazolium bromide (MTT) assay. A 0.25%, 0.5%, 1%, and 5% (v/v) plain or purple sweet potato yogurt supernatant was given to 3T3-L1 preadipocyte culture medium from 24 h after seeding until day 11 of MDI-induced differentiation. The mRNA expression and lipid accumulation were analyzed using RT-qPCR and Oil red O staining, respectively, on day 11 after differentiation induction.Results: In silico study suggested that anthocyanin-derived compounds have the potential to inhibit peroxisome proliferator activated receptor gamma (PPAR-γ), a master regulator for white adipogenesis. Anthocyanin-containing PSPY significantly suppressed the expression of Pparg, Adipoq, Slc2a4, and Pgc1a. PSPY significantly suppressed Pparg with 1% and 5% concentrations, while with a concentration of 0.25%, PSPY significantly suppressed Adipoq expression as compared to control. Significant inhibition of Slc2a4 and Pgc1a was observed starting from a 0.25% concentration of PSPY. The suppression of adipogenic genes was also observed with the treatment of plain yogurt; however, the effects were relatively lower than the PSPY. The group treated with 1% and 5% of PSPY also showed inhibition effects on lipid accumulation.Conclusion: This study demonstrated PSPY inhibition effect on white adipocyte differentiation through suppression of Pparg and its downstream genes, Adipoq and Slc2a4, indicating the potential of this yogurt as a functional food for obesity management and prevention.Keywords: adipocyte differentiation, anthocyanin, Pparg, purple sweet potato synbiotic yogurt